Unveiling the consequences of esg rating disagreement: An empirical analysis of the impact on the cost of equity capital - Chiara Mio; Marco Fasan; Antonio Costantini; Francesco Scarpa; Aoife Claire Fitzpatrick (Leibniz Institute for Financial Research SAFE, 2024)
Recent academic research exhibits considerable disagreement among ESG ratings from different agency providers. The consequences of this disagreement on the market are still under-explored; thus, we investigate whether this disagreement impacts the cost of equity capital. Using a sample of 23,201 firm-month observations from January 2019 to March 2021, we find that ESG disagreement positively moderates the negative relationship between the average ESG score and cost of equity. By disentangling the aggregate ESG score, we find that the moderating effect of this disagreement does not hold for any pillar. Furthermore, the association between ESG rating disagreement and cost of equity is more pronounced in the presence of high analyst information uncertainty. Overall, our findings highlight that ESG rating disagreement jeopardizes investors' confidence in ESG ratings and weakens the role of these ratings in reducing the cost of equity, pointing to the need to improve convergence across agency providers.
Keywords: 330; ESG; rating; disagreement; information uncertainty; cost of equity capital